Aerodynamic Study of a Two Groove on the Upper Surface of an Airfoil at Low Angles of Attack - Abdullah, Esmail; Yaakub, Mohd Fauzi; Azman, Muhammad Aideed; Wan Nawang, Wan Muhammad Aqil (Progress in Aerospace and Aviation Technology, 2025)
This study investigates the aerodynamic effects of introducing two semicircular grooves on the upper surface of a NACA 0012 airfoil at low angles of attack using computational fluid dynamics (CFD). The purpose of this research is to evaluate how groove geometry, depth, and spacing influence the lift and drag characteristics and to determine the optimal groove configuration that enhances aerodynamic performance. ANSYS Fluent was utilized to simulate the airflow over a baseline smooth airfoil and modified versions featuring grooves of varying sizes and positions. A grid independence test was conducted to ensure the accuracy and numerical reliability of the simulation. The baseline airfoil simulation was validated against experimental data, showing good agreement with a maximum relative error of less than 10%. The results revealed that a single groove of 0.01c depth provided an increase in lift and a notable drag reduction, particularly at a 10° angle of attack. Further investigations with two grooves, where the first groove was fixed at 0.25c and the second varied between 0.239c and 0.45c, showed that the optimal configuration was with the second groove placed at 0.35c. The study concludes that proper groove positioning and sizing can effectively delay flow separation, enhance lift, and reduce drag in low-speed aerodynamic applications. These findings suggest potential benefits for UAVs, gliders, and other airfoil-based systems operating at low angles of attack.